Osteopontin induced vascular endothelial growth factor production in dispersed nasal polyp cells through the phosphatidylinositol 3-kinase-protein kinase B and the extracellular signal-regulated kinase 1/2 pathways - Du, Jingdong; Mao, Huadong; Ouyang, Hong; Xin, Yan (American journal of rhinology & allergy, 2017)
Osteopontin (OPN) is involved in cell survival, migration, and angiogenesis. The role of OPN in inducing angiogenesis in tumor has been confirmed. In this study, we investigated the expression of OPN in patients with chronic rhinosinusitis (CRS) with nasal polyp (NP) and the relationship of OPN with vascular endothelial growth factor (VEGF) production. We enrolled 45 subjects with CRS (25 with CRS with NPs [CRSwNP] and 20 subjects with CRS without NPs [CRSsNP]), and with 14 normal controls to determine the expression of OPN and VEGF. The distribution, messenger RNA (mRNA), and protein levels of OPN and VEGF were examined by immunohistochemistry, quantitative polymerase chain reaction, and enzyme-linked immunosorbent assay, respectively. The effect of OPN on the VEGF production was tested in dispersed NP cells (DNPC) and the involved signaling pathways were examined by Western blot. In NP tissue of the subjects with CRSwNP, the epithelial cells, interstitial cells, glandular cells, and endothelial cells were positive for OPN and VEGF staining, whereas OPN and VEGF immunoactivity in specimens of subjects with CRSsNP and in normal controls was significantly reduced. We found that the immunostainings, the mRNA expression, and the protein levels of OPN and VEGF were significantly increased in NPs compared with normal controls. OPN induced VEGF production by DNPCs in a time- and dose-dependent manner through phosphatidylinositol 3-kinase- protein kinase B and the extracellular signal-regulated kinase 1/2 pathway. Moreover, VEGF also induced OPN production, which formed a positive feedback between OPN and VEGF. Our findings demonstrated that OPN and VEGF were overproduced in NPs and that OPN induced VEGF production, which indicated that OPN-VEGF axis might contribute to angiogenesis in NPs.